(3VeGfGJ GdJCOjH aj GdhXjaI GdYGeI aj GdbGfhf GddjHj hGdebGQf (B/s - (3GdTdeGfj, MeO eMeO MeOs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdeWHhYGJ GdLGeYjI,s, 2014)
(3JgOa gPg GdOQGSI ddESgGe aj EjLGO eQLY aj eLGd fXGe GdJCOjH, hHNGUI ajeG jJYdb HVeGfGJ GdJCOjH aj GdhXjaI GdYGeI aj djHjG ebGQfI HGdCfXeI GdCNQi, Pdc Cf bVGA GdJCOjH jge TQjMI cHjQI ef GdeLJeY, gj TQjMI GdehXajf, GdJj JVGgi aj GdCgejI GdbVGA GdLfGFj, GdPj CMGW GdeTQhY ajg GdeJge HYOI VeGfGJ, ShGA aj eQMdI GdJMbjb Ch aj eQMdI GdeMGceI, hJJfGhd gPg GdOQGSI GdJCOjH aj fWGb GdhXjaI GdYGeI, NGUI aj GdbGfhf GddjHj hGdeUQj, eY GdETGQI Edi GdbGfhf GdaQfSj HGdbOQ GdPj jJjM eLGdG ddebGQfI aj ehVhY GdHMK(B. (3hJfGhd gPG GdcJGH gPG GdehVhY MSH GdaUhd hGdeHGMK GdJGdjI (B: (3aUd JegjOj (B: (3GdJYQja HGdfXGe GdJCOjHj hWHjYJg GdbGfhfjI, GdeHMK GdChd (B: (3GdJYQja HGdbGfhf GdJCOjHj hGdLQjeI GdJCOjHjI, GdeHMK GdKGfj (B: (3GdCSGS GdbGfhfj ddJCOjH, GdeHMK GdKGdK (B: (3WHjYI GdJCOjH GdbGfhfjI(B. (3GdaUd GdChd (B: (3VefGJ GdJMbjb hGdeMGceI GdJCOjHjI, GdeHMK GdChd(B: (3VeGfGJ GdJMbjb, GdeHMK GdKGfj (B: (3VeGfGJ GdeMGceI GdJCOjHjI(B. (3GdaUd GdKGfj (B: (3GdQbGHI GdbVGFjI Ydi bQGQGJ GdSdWGJ GdJCOjHjI, GdeHMK GdChd(B: (3GdQbGHI GdbVGFjI aj GdbGfhf GddjHj, GdeHMK GdKGfj(B: (3GdQbGHI GdbVGFjI aj GdbGfhf GdeUQj(B.s
(3HHdjhLQGajI (B: (3UaMI (B321-327.s
Keywords: (3GfVHGW GdYeds -- (3bhGfjf hJTQjYGJs -- (3djHjGs; (3GdehXahfs -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3djHjGs